POLA ASUH ORANG TUA TUNGGAL DALAM PENDIDIKAN AGAMA ISLAM - Hasna Koba'a (Universitas Negeri Gorontalo, 2021)
The role of parent in the moral development of children is determined by the parenting pettern performed by single parentThe purpose of this study was to determine the parenting pattern of single parent in Islamic education. This research used descriptive analysis, described the facts in the field, then it was analyzed based on educational theories combined with data collection techniques through observation, interviews and questionnaires. The results of the study, there were three types of parenting styles used by single parent in Bantayan Village, 10 people used democratic parenting, 12 people used liberal/permissive parenting, and 4 people used authoritarian parenting. The single parent in Bantayan Village tended to use liberal/permissive parenting in educating their children, due to low educational and economic factors. The liberal/permissive parenting given by single parent to children had several influences on children’s behavior. Children though that the relationship with parents was only limited to material fulfillment, children act appropriate to their own will and the child become difficult to be guided.